Non-viral expression of chimeric antigen receptors with multiplex gene editing in primary T cells - Cappabianca, Dan; Li, Jingling; Zheng, Yueting; Tran, Cac; Kasparek, Kassandra; Mendez, Pedro; Thu, Ricky; Maures, Travis; Capitini, Christian M.; Deans, Robert; Saha, Krishanu (Frontiers in Bioengineering and Biotechnology, 2024)
Efficient engineering of T cells to express exogenous tumor-targeting receptors such as chimeric antigen receptors (CARs) or T-cell receptors (TCRs) is a key requirement of effective adoptive cell therapy for cancer. Genome editing technologies, such as CRISPR/Cas9, can further alter the functional characteristics of therapeutic T cells through the knockout of genes of interest while knocking in synthetic receptors that can recognize cancer cells. Performing multiple rounds of gene transfer with precise genome editing, termed multiplexing, remains a key challenge, especially for non-viral delivery platforms. Here, we demonstrate the efficient production of primary human T cells incorporating the knockout of three clinically relevant genes (B2M, TRAC, and PD1) along with the non-viral transfection of a CAR targeting disialoganglioside GD2. Multiplexed knockout results in high on-target deletion for all three genes, with low off-target editing and chromosome alterations. Incorporating non-viral delivery to knock in a GD2-CAR resulted in a TRAC-B2M-PD1-deficient GD2 CAR T-cell product with a central memory cell phenotype and high cytotoxicity against GD2-expressing neuroblastoma target cells. Multiplexed gene-editing with non-viral delivery by CRISPR/Cas9 is feasible and safe, with a high potential for rapid and efficient manufacturing of highly potent allogeneic CAR T-cell products.